Pengembangan Instrumen Tes Keterampilan Proses Sains Pada Materi Fisika - Siregar, Zulfikri; Harahap, Aminah (Institut Agama Islam Negeri Padangsidimpuan, 2024)
Development is an effort to improve technical, theoretical, conceptual and moral abilities according to needs through education and training. So development is more realistic, not just idealistic. Education is difficult to apply in life, development is an effort to improve quality both in terms of material and its substitutes. The research aims to produce an assessment instrument to measure scientific process skills in optical materials, pressure and wave vibrations. The research instrument is a question feasibility test questionnaire addressed to validators and a student response questionnaire. The research subjects were 30 students of class XI IPA1 SMA Negeri 1 Batangtoru in Batangtoru Dis. The test developed is in the form of reasoned multiple choice and essay. The research results show that: (1) The validity or feasibility of the PPP instrument developed based on experts is valid and suitable for use; (2) Validity of the PPP assessment instrument items developed with valid criteria; (3) The reliability of the questions from the KPS instrument is very strong for multiple choice questions on optics and wave vibrations; strong reliability for pressure material questions; and moderate reliability for essay questions on elasticity, fluids, Newton's laws and wave vibrations; and (4) The questions questions with a medium level of difficulty